2020
DOI: 10.2147/amep.s188258
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Use of in situ Simulation in Healthcare Education: Current Perspectives</p>

Abstract: In situ simulation is the practice of using simulated scenarios in a clinical environment itself rather than in training facilities to promote learning and improved clinical care. The use of in situ simulation has been increasingly used to train healthcare staff in dealing with emergencies, resuscitation and clinical skills. The aim of this study is to provide an overview of the themes, perspectives and approaches to in situ simulation for educational purposes with healthcare staff. The literature search inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 40 publications
0
24
0
3
Order By: Relevance
“…We suggest that in situ simulation may enhance students' PVC learning and improve their success when performing the skill on patients, as the simulations take place during clinical placement, not just in simulation centres. In the clinical setting in situ implies an opportunity to simulate tasks and situations in the actual practise setting (Martin et al, 2020). Hospital staff who simulated a scenario involving cardiac arrest reported that the training was more realistic because it was performed in a clinical setting (Walker et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We suggest that in situ simulation may enhance students' PVC learning and improve their success when performing the skill on patients, as the simulations take place during clinical placement, not just in simulation centres. In the clinical setting in situ implies an opportunity to simulate tasks and situations in the actual practise setting (Martin et al, 2020). Hospital staff who simulated a scenario involving cardiac arrest reported that the training was more realistic because it was performed in a clinical setting (Walker et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, in situ simulation-based PVC practise on a latex arm immediately following a failed PVC attempt on a patient's arm could improve students' awareness and knowledge of the different aspects of the learning task, and they are given opportunities to receive supervision throughout the entire attempt of PVC. In situ simulation has been found to enhance clinical competence and improve patient safety, also in skill learning (Martin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SBR in the context of healthcare involves replicating clinical scenarios, with the aim of eliciting reactions and behaviors from healthcare professionals that are as close as possible to how they would react in a real situation 25 . SBR may take place in situ (i.e., in a clinical setting), where they can be announced or unannounced (i.e., participating staff are aware that a simulated event will take place but may or may not be informed as to when), or in dedicated simulation spaces away from the clinical setting [26][27][28] and color (e.g., "GREEN") or incongruent (e.g., "RED").…”
Section: Existing Applications Of Simulation-based Research (Sbr) Methods In Healthcare Contextsmentioning
confidence: 99%
“…In situ simulation increases individual training and inter-professional collaboration and enhances soft skills such as communication, leadership, and membership. Moreover, in situ simulation creates the possibility to simulate in the real environment, providing stressful training in a safe context for high-risk procedures (Martin et al, 2020).…”
Section: The Role Of Simulation and Experiential Learning In Diving And Hyperbaric Medicinementioning
confidence: 99%